(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
It has long been recognized that education was among the most important determinants in a country’s economic growth. A developed country is always a well-educated country. As a result, the learning process should be altered by current needs and indeed the globalized context. After the United States and China, India has the world’s third-largest higher education sector. Since freedom, India has struggled to make progress in the area of education as a developing country. Following independence, India’s higher education sector has seen a huge influx of universities and colleges. The private sector’s engagement in academia has been a game-changer for such rapid expansion. This same Right to Education Legislation has ushered in a sea shift in India’s educational system. As India’s Higher Education System has faced several concerns and challenges, it also has numerous chances to overcome these obstacles and improve the system. The function of schools and colleges in the new century, as well as rising scientific knowledge on how individuals learn, all need increased openness and accountability. India needs highly qualified and educated individuals who can propel our economy ahead. According to study, just 25% of engineering graduates are immediately employable, and most institutions’ educational quality is inadequate. Neither Indian university has ever been ranked among the top 200 universities in the world. This study analyses the current state of higher education, as well as identifying new concerns and challenges in the sector. Finally, this study proposes a viable response in Higher Ed to developing concerns and challenges.